2021
DOI: 10.2147/dddt.s301679
|View full text |Cite
|
Sign up to set email alerts
|

Potential Mechanism of S. baicalensis on Lipid Metabolism Explored via Network Pharmacology and Untargeted Lipidomics

Abstract: Background S. baicalensis , a traditional herb, has great potential in treating diseases associated with aberrant lipid metabolism, such as inflammation, hyperlipidemia, atherosclerosis and Alzheimer’s disease. Aim of the Study To elucidate the mechanism by which S. baicalensis modulates lipid metabolism and explore the medicinal effects of S. baicalensis at a holistic level. Materials a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Nevertheless, in comparison with the precise clinical efficacy and the long history of the application of TCM, there is a relative lack of research on the mechanism of TCM. Accordingly, considering the multicomponent and multitarget characterization of TCM, the method of network pharmacology has been applied to study the potential mechanism of TCM and a series of progress was accomplished [ 40 , 41 ]. In our current study, we initially explored the potential mechanism of BXD on CAG via the method of network pharmacology considering the definitive clinical efficacy of BXD.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in comparison with the precise clinical efficacy and the long history of the application of TCM, there is a relative lack of research on the mechanism of TCM. Accordingly, considering the multicomponent and multitarget characterization of TCM, the method of network pharmacology has been applied to study the potential mechanism of TCM and a series of progress was accomplished [ 40 , 41 ]. In our current study, we initially explored the potential mechanism of BXD on CAG via the method of network pharmacology considering the definitive clinical efficacy of BXD.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that baicalin can regulate lipid metabolism, oxidative stress, calcium homeostasis and endoplasmic reticulum stress of host ( Cao et al, 2018 ; Ishfaq et al, 2019a ; Wang et al, 2020 ; Yu et al, 2020 ). For example, according to a network pharmacology study, S. baicalensis may exert its beneficial effects by regulating the cholesterol biosynthesis and sphingolipid metabolism pathways of host, and baicalin, a major ingredient of S. baicalensis , may regulate lipid metabolism by inhibiting activities of key enzymes such as squalene monooxygenase and lanosterol synthase ( Ge et al, 2021 ). In addition, baicalin can alleviate oxidative stress and endoplasmic reticulum stress via Nrf2 signaling pathway activation ( Lin et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Caco-2 screening assay is a valuable tool for testing compounds for intestinal permeability [ 17 ]. In this study, the criteria of OB ≥30%, DL ≥0.18, and Caco-2 ≥ -0.4 were used to screen the active components from TCMSP [ 18 ]. The canonical SMILES of components from TCMID and TCM@Taiwan databases were imported into SwissADME website ( http://www.swissadme.ch/ ) to analyze the bioavailability score.…”
Section: Methodsmentioning
confidence: 99%